An Optical-Fiber Based Sensor Array for the Simultaneous Analysis of Zinc and Copper in Aqueous Environments - (:unkn) unknown (My University, 2013)
Copper and zinc are elements commonly used in industrial applications, with many of these processes using these elements in aqueous environments. Before the solutions can be discharged into civil or native waterways, waste treatment processes must be undertaken to ensure compliance with federal, state and local guidelines restricting the concentration of ions discharged in solution. While there are methods of analysis currently available to monitor these solutions, each method has disadvantages, be it that they are cost prohibitive, inaccurate, and/or time-consuming. In this work, a new optical fiber-based platform capable of providing fast and accurate results when performing solution analysis for these metals is described. Using fluorescent compounds that exhibit a high sensitivity and selectivity for either zinc or copper have been employed for fabricating the sensors. These sensors demonstrated sub-part-per-million detection limits, 30-second response times, and the ability to analyze samples with an average error of under 10%. The inclusion of a fluorescent compound acting as a reference material to compensate for fluctuations from pulsed excitation sources has further increased the reliability and accuracy of each sensor. Finally, after developing sensors capable of monitoring zinc and copper individually, these sensors can be combined to form a single optical fiber sensor array capable of simultaneously monitoring concentration changes in zinc and copper in aqueous environments.
Keywords: Fluorescence; Heavy Metals; Optical Fibers; Sensors